2022
DOI: 10.1016/j.resuscitation.2021.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers associated with mortality in pediatric patients with cardiac arrest and acute respiratory distress syndrome

Abstract: Aim of the Study:To identify plasma biomarkers associated with cardiac arrest in a cohort of children with acute respiratory distress syndrome (ARDS), and to assess the association of these biomarkers with mortality in children with cardiac arrest and ARDS (ARDS + CA).Methods: This was a secondary analysis of a single-center prospective cohort study of children with ARDS from 2014-2019 with 17 biomarkers measured. Clinical characteristics and biomarkers were compared between subjects with ARDS + CA and ARDS wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Early studies in patients examined the association of levels of single biomarkers with outcomes; however, the complexity of the pathobiology and biomarker changes suggested that this approach may be too simplistic. Since the publication of the first PALICC consensus recommendations, a number of studies have evaluated multiple plasma biomarkers (including many of those described above) and examined their relationship to other biomarkers and/or their relationship to the development or outcomes of PARDS (102–104, 107, 108, 114, 118, 122, 127, 128, 130, 131, 154–157). Approaches have included evaluating multiple biomarkers in regression models (108, 109), classification and regression tree analysis with mortality as the outcome (77, 131), and generating biomarker profiles (118, 158).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies in patients examined the association of levels of single biomarkers with outcomes; however, the complexity of the pathobiology and biomarker changes suggested that this approach may be too simplistic. Since the publication of the first PALICC consensus recommendations, a number of studies have evaluated multiple plasma biomarkers (including many of those described above) and examined their relationship to other biomarkers and/or their relationship to the development or outcomes of PARDS (102–104, 107, 108, 114, 118, 122, 127, 128, 130, 131, 154–157). Approaches have included evaluating multiple biomarkers in regression models (108, 109), classification and regression tree analysis with mortality as the outcome (77, 131), and generating biomarker profiles (118, 158).…”
Section: Resultsmentioning
confidence: 99%
“…Mortality has been associated with a sepsis-like host-response profile characterized by systemic inflammation and altered metabolism linked to bioenergetic deficits 2,[19][20][21][22] . In sepsis, mortality has been linked to immunoparalysis, organ damage including the cardiac, respiratory, hepatic and renal systems, uncontrolled inflammation, proteolysis, and defects of organ healing capability [23][24][25][26][27][28][29][30][31][32][33][34] . Mitochondrial and peroxisomal dysfunction involves kynurenine derivatives including intermediates of redox cofactors nicotinamide adenine dinucleotide (NAD), acylglycerophosphocholines, acyl-carnitines, and bile acids.…”
Section: Systemic Inflammation and Altered Metabolismmentioning
confidence: 99%
“…Recognizing the need for rapid, point-of-care diagnostics for sepsis subgroup stratification, he developed the PERSEVERE-II biomarker panel (5, 6), which is in the process of commercialization. His work has served to develop risk stratification strategies in sepsis-associated acute kidney injury (7), myocardial dysfunction (8), and acute respiratory distress syndrome (9, 10). He was adept at moving from bedside to bench, leveraging his findings in sepsis genomic data to elucidate the role of matrix metalloproteinase-8 (11, 12), olfactomedin-4 (13), and interleukin-27 (14), among others in sepsis pathophysiology.…”
mentioning
confidence: 99%